Pengaruh Kredibilitas Celebrity Endorser, Daya Tarik Iklan Dan Kepuasan Pelanggan Terhadap Ekuitas Merek (Brand Equity) Dari Produk Sampo L'oreal Pada Konsumen Wanita (Studi Kasus Di Kota Denpasar) - Pracista, Ni Muni; Rahanatha, Gede Bayu (E-Jurnal Manajemen, 2014)
This research aim to determine the influence celebrity endorser credibility, attraction advertising and customer satisfaction to brand equity (brand equity) from L'oreal shampoo products on the female consumer in Denpasar with a sample size of 140 respondents taken by purposive sampling method. Data be obtained through questionnaires with 5-point Likert scale to measure 14 indikator.Teknik analysis used is multiple linear regression. This research has resulted that each variable celebrity endorser credibility, attraction advertising and customer satisfaction and a significant positive effect on brand equity (brand equity). Advice for companies and marketers are in the selection of the endorser must have good credibility, as well as ads that appear able to create an emotional bond with the audience and increase customer satisfaction by maintaining consistency of the quality of the product.